ChemInform Abstract: Structural, Hyperfine and Raman Properties of RE2FeSbO7 Compounds. Issue 52 (29th December 2014) - Berndt, G.; Silva, K. L.; Ivashita, F. F.; Paesano, A. Jr.; Blanco, M. C.; Miner, E. V. P.; Carbonio, R. E.; Dantas, S. M.; Ayala, A. P.; Isnard, O.
Abstract Pyrochlores of the Ln2FeSbO7 type (Ln: Y, Pr—Er, Yb) are prepared by ball‐milling of Ln2O3, α‐Fe2O3, and Sb2O5 in the molar ratio of 2:1:1, followed by annealing (1200—1400 °C, 6 h).